Perspectives on Libraries as Institutions of Human Rights and Social Justice. - Ursula Gorham; Natalie Greene Taylor; Paul T. Jaeger (Advances in Librarianship,, 2016)
Academic, public, school, and special libraries are all institutions of human rights and social justice, with an increasingly apparent commitment to equality, to ethical principles based on rights and justice, and to programs that meet needs related to human rights and social justice. Key topics at the intersection of information, human rights, social justice, and technology include information access and literacy, digital inclusion, education, and social services, among many others. Edited by Ursula Gorham, Natalie Greene Taylor, and Paul T. Jaeger, this volume is devoted to the ideals, activities, and programs in libraries that protect human rights and promote social justice. With contributions from researchers, educators, and practitioners from a range of fields, this book is an important resource for library professionals in all types of libraries, a reference for researchers and educators about all types of libraries, and an introduction to those in other fields about the contributions of libraries to human rights and social justice.